The Role of Home Physical Environment and Family Behavior in Preventing Pneumonia among Under-Five Children in a High-Density Urban Area of Jakarta, Indononesia - Rojali Rojali; Indah Restiaty; Haerlintiniyah Huriyandah; Cecep Dani Sucipto (International Journal of Health Engineering and Technology, 2026)
This study aimed to examine the association between home physical environmental conditions, family behavior, and pneumonia occurrence among under-five children in a high-density urban area of Jakarta, Indonesia. A cross-sectional analytical study was conducted in RW 14, Cengkareng Barat, West Jakarta. Data were collected from caregivers of 60 under-five children using structured questionnaires and observational checklists. Associations were analyzed using chi-square tests, and prevalence ratios (PR) were calculated. Seventeen children (28.3%) had a history of pneumonia. Bedroom occupancy density was significantly associated with pneumonia occurrence (p = 0.002), with adequate occupancy density showing a protective effect (PR = 0.094; 95% CI: 0.013–0.678). Family smoking behavior was also significantly associated with pneumonia occurrence (p = 0.033; PR = 1.85; 95% CI: 1.02–3.36). Other household environmental factors were not statistically significant (p > 0.05). Overcrowded sleeping conditions and indoor smoking behavior are key household determinants of pneumonia among under-five children in densely populated urban settings. Household-focused preventive interventions addressing overcrowding and smoke-free homes should be prioritized.